Graphene—vertically aligned carbon nanotube hybrid on PDMS as stretchable electrodes. (23rd October 2017) - Ding, Junjun; Fu, Shichen; Zhang, Runzhi; Boon, Eric; Lee, Woo; Fisher, Frank T; Yang, Eui-Hyeok
Abstract: Stretchable electrodes are a critical component for flexible electronics such as displays, energy devices, and wearable sensors. Carbon nanotubes (CNTs) and graphene have been considered for flexible electrode applications, due to their mechanical strength, high carrier mobility, and excellent thermal conductivity. Vertically aligned carbon nanotubes (VACNTs) provide the possibility to serve as interconnects to graphene sheets as stretchable electrodes that could maintain high electrical conductivity under large tensile strain. In this work, a graphene oxide (GO)-VACNT hybrid on a PDMS substrate was demonstrated. Here, 50 μ m long VACNTs were grown on a Si/SiO2 wafer substrate via atmospheric pressure chemical vapor deposition. VACNTs were directly transferred by delamination from the Si/SiO2 to a semi-cured PDMS substrate, ensuring strong adhesion between VACNTs and PDMS upon full curing of the PDMS. GO ink was then printed on the surface of the VACNT carpet and thermally reduced to reduced graphene oxide (rGO). The sheet resistance of the rGO-VACNT hybrid was measured under uniaxial tensile strains up to 300% applied to the substrate. Under applied strain, the rGO-VACNT hybrid maintained a sheet resistant of 386 ± 55 Ω/sq. Cyclic stretching of the rGO-VACNT hybrid was performed with up to 50 cycles at 100% maximum tensile strain, showing no increase in sheet resistance. These results demonstrate promising performance of the rGO-VACNT hybrid for flexible electronics applications.